2010
DOI: 10.1007/s11033-010-0294-9
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in 5′-flanking regions of genes encoding adiponectin, leptin, and resistin are not associated with obesity of Polish children and adolescents

Abstract: Genes encoding adipokines are important functional candidates for development of obesity. In this study we screened for polymorphism 5'-flanking regions of the adiponectin (ADIPOQ), leptin (LEP) and resistin (RETN) genes in a cohort of Polish obese children and adolescents (n = 243) and a control group of non-obese adults (n = 100). Altogether 13 SNPs (single nucleotide polymorphisms) and 1 InDel (insertion/deletion polymorphism) were found. Among them five polymorphisms, localized in the LEP gene, turned out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
3
11
0
Order By: Relevance
“…However, there have been reports of differences in the frequencies of the 420C/G in other ethnic groups (Mattevi et al, 2004;Onuma et al, 2010;Chen et al, 2010;Cieslak et al, 2011). For the 44G/A and 62G/A polymorphisms, the frequencies of the AA genotype were < 3% in our study; these results were also reported in other populations (Cao and Hegele, 2001;Sentinelli et al, 2002;Conneely et al, 2004;Gouni-Berthold et al, 2005;Duman et al, 2007).…”
Section: Discussionsupporting
confidence: 61%
“…However, there have been reports of differences in the frequencies of the 420C/G in other ethnic groups (Mattevi et al, 2004;Onuma et al, 2010;Chen et al, 2010;Cieslak et al, 2011). For the 44G/A and 62G/A polymorphisms, the frequencies of the AA genotype were < 3% in our study; these results were also reported in other populations (Cao and Hegele, 2001;Sentinelli et al, 2002;Conneely et al, 2004;Gouni-Berthold et al, 2005;Duman et al, 2007).…”
Section: Discussionsupporting
confidence: 61%
“…Although no studies have analyzed the association of the rs10401670 SNP with anthropometric variables, contradictory results can also be found in previous studies of other polymorphisms in the resitin gene in adults [24-26, 28, 33, 34]. The study by Cieslak et al [29], which examines the relationship of the several polymorphisms in the resistin gene with obesity in Polish children, failed to find any significant association. Unfortunately, we do not have data on body fat composition from a sufficiently large sample so as to analyze the association of these SNPs with body fat mass.…”
Section: Discussionmentioning
confidence: 93%
“…However, studies in other populations have failed to find an association with anthropometric variables [22,24,28] or lipid profile [17,19,25]. The association of the SNP rs1862513 with obesity has also been the subject of studies in children [29], but to our knowledge its association with lipid levels has not been investigated in this age group.…”
Section: Introductionmentioning
confidence: 94%
“…For all the 48 patients genotypes at five polymorphic sites (three in LEP and two in ADIPOQ ) in the 5′-flanking regions of both genes were established in our earlier study [14]. The comparison of gene expression, including all the three genotypes (two alternative homozygotes and a heterozygote) was possible only for the three most common SNPs, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…There are also reports indicating an association between obesity and some polymorphisms in the 5′-flanking regions of the leptin ( LEP ) and adiponectin ( ADIPOQ ) genes; however, the conclusions are not consistent [913]. In our recent studies of obese children and adolescents we detected 9 polymorphic sites in the 5′-flanking region of the LEP and 2 in the 5′-flanking region of the ADIPOQ genes [14], but the frequency of these variants did not differ in a cohort of obese patients when compared with non-obese ones. The effect of polymorphism in the 5′-flanking regions of genes encoding adiponectin and leptin was reported in several studies.…”
Section: Introductionmentioning
confidence: 89%